Analysis Of Passive Heat Removal System Through Steam Generator - Petrosyan, Taron (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
In the current study, the model of Passive Heat Removal System (PHRS) through Steam Generator (SG) was developed for computational fluid dynamics (CFD) analysis. During work there was done three main tasks, which are creating geometrical form of PHRS, meshing of model to achieve a better analysis of thermal-hydraulic phenomena and creating domains for simulation steam condensation in PHRS SG heat exchanger tubes. Analysis through the "ANSYS CFX" software, with two different cases investigated at the steam inlet velocity of 1 m/s and 3 m/s. A thorough description of the steam condensation process in the passive cooling system obtained as a result of the analysis. The rate of the steam condensation in heat exchanger pipeline was assessed.
Keywords: PHRS; CFD; ANSYS; CFX; thermal-hydraulics; NPP